Nuclear disarmament regional perspectives on progress - Kamath, P. M. (Emerald, 2013)
This volume presents a range of views on the current state of global nuclear disarmament from eminent scholars from India, Israel and France. Chapters present and analyse the relationships between India, Pakistan and the USA, Russia and the USA, the position of the EU and of Israel. The perspectives presented range from optimism to pessimism on global nuclear disarmament and consequences for human security.
Includes index.
Keywords: Political Science -- Peace.; Political Science -- Political Freedom & Security -- International Security.; Political Science -- General.; Peace studies & conflict resolution.; Peacekeeping operations.; Nuclear disarmament.; Nuclear arms control.; elektronické knihy; electronic books